Management outcome and risk factor in children with severe acute malnutrition in - Kankane, Aradhna; Lalwani, Deepak; Chhabra, Kawalpreet; Chaurasiya, Om Shankar (Indian Journal of Child Health, 2022)
Aim: The aim of the study was to study management outcomes and risk factors in children with Severe Acute Malnutrition (SAM)